Voltage-gated and stretch-activated potassium channels in the human heart - Schmidt, Constanze; Peyronnet, Remi (Herzschrittmachertherapie + Elektrophysiologie, 2018)
Ion channels are essential for electrical signaling and contractility in cardiomyocytes. Detailed knowledge about the molecular function and regulation of cardiac ion channels is crucial for understanding cardiac physiology and pathophysiology especially in the field of arrhythmias. This review aims at providing a general overview on the identity, functional characteristics, and roles of voltage-gated as well as stretch-activated potassium selective channels in the heart. In particular, we will highlight potential therapeutic targets as well as the emerging fields of future investigations.
Published: 05 January 2018
Gesehen am 26.03.2020